Prevalensi dan Faktor Risiko Infeksi Parasit Usus Non-STH, Khususnya Enterobius Vermicularis, pada Anak Usia 1-5 Tahun di Kota Kupang - Aldina Astuti; Lidia Wangak; Wilhelmus Olin (Inovasi Kesehatan Global, 2025)
Intestinal parasitic infections caused by non-Soil Transmitted Helminths (non-STH), particularly Enterobius vermicularis, remain a public health problem in developing countries, including Indonesia. Transmission does not require soil as a medium but occurs through direct contact, autoinfection, or unclean household environments. In children, infection may cause perianal itching, sleep disturbances, loss of appetite, and secondary infections due to scratching, which can affect nutritional status, sleep quality, and overall growth and development. This study was conducted in Kupang City, an endemic area of helminthiasis, to determine the prevalence and risk factors of E. vermicularis infection among children aged 1–5 years. A cross-sectional design with total sampling was applied to 30 children living in RT 008/RW 003, Penfui Timur Village, Kupang Tengah District, from February to May 2025. Risk factor data were collected using structured questionnaires covering personal hygiene, environmental sanitation, socioeconomic status, and parental education. Infection was identified using the scotch tape technique and microscopic examination. The results showed a prevalence of 7% (2 out of 30 children), mainly among boys aged ≥4 years, with poor personal hygiene, inadequate sanitation, low economic status, and parental education at elementary school level or below. In conclusion, enterobiasis in children is influenced by a combination of behavioral, environmental, and socioeconomic factors. Prevention should not rely solely on mass deworming programs but also require continuous health education for parents, improved hygiene practices, and household sanitation.